Ternary positive electrode material, preparation method thereof and electrochemical device

By forming a cladding layer of cationic disordered salt lithophase structure on the inner core surface of the nickel-cobalt-manganese ternary cathode material, the problem of material structure failure under high voltage is solved, the structural and interface stability of the material is improved, and the battery is extended Cycle life.

CN119481013APending Publication Date: 2025-02-18XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746467.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Nickel-cobalt-manganese ternary cathode material is prone to side reactions with the electrolyte under high working voltage conditions, resulting in structural damage and performance degradation, making it difficult to meet the needs of high voltage use.

Method used

A cladding layer of cationic disordered salt lithophagometer structure is formed on the inner core surface of the ternary positive electrode material. The cladding layer contains redox pairs, and the molar concentration of divalent ions is greater than that of trivalent ions.

Benefits of technology

Through the design of the cladding layer, the structural stability and interface stability of the ternary positive electrode material under high voltage are improved, the generation of cracks and interface side reactions are reduced during the cycle, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481013A_ABST
    Figure CN119481013A_ABST
Patent Text Reader

Abstract

The invention relates to a ternary positive electrode material, a preparation method thereof and an electrochemical device, the ternary positive electrode material comprises an inner core and a coating layer located on the surface of the inner core, the coating layer has a cation disordered salt rock phase structure, the coating layer contains a first coating element, the first coating element exists in the form of a redox couple, and the first coating element has a cation disordered salt rock phase structure. The valence states of two ions in the redox pair are respectively divalent and trivalent, and the molar concentration of the divalent ions in the redox pair is greater than that of the trivalent ions. According to the ternary positive electrode material provided by the invention, the structural stability and the interface stability of the ternary positive electrode material can be effectively improved, and the ion diffusion rate and the electronic conductivity of the ternary positive electrode material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy materials, and in particular to a ternary positive electrode material, a preparation method thereof, and an electrochemical device. Background Art

[0002] Lithium-ion batteries are widely used in 3C digital products, vehicle power systems, power station energy storage and other fields due to their advantages such as high energy density and long cycle life. As an important component of the battery, the performance of the positive electrode material directly affects the overall performance of the battery. Among them, nickel-cobalt-manganese ternary materials have become a hot topic of current research due to their high theoretical capacity, good thermal stability and high comprehensive performance.

[0003] However, with the rapid development of electric vehicles and large-scale energy storage, nickel-cobalt-manganese ternary cathode materials are gradually developing towards high voltage. Under high working voltage conditions, nickel-cobalt-manganese ternary materials are prone to side reactions with the electrolyte, transition metals in the cathode materials are easily dissolved, and lattice oxygen escape and lattice strain are prone to occur, resulting in the destruction of the layered structure, etc., making it difficult to meet the high voltage requirements. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a ternary positive electrode material that can maintain stable performance and structure during the charging and discharging process and even at a high operating voltage.

[0005] In addition, the embodiments of the present application also provide a method for preparing the aforementioned ternary positive electrode material and an electrochemical device using the ternary positive electrode material.

[0006] An embodiment of the present application provides a ternary positive electrode material, which includes: an inner core and a coating layer located on the surface of the inner core, wherein the coating layer has a cationic disordered salt rock phase structure, wherein the coating layer contains a first coating element, and the first coating element exists in the form of a redox pair, the valence states of the two ions in the redox pair are divalent and trivalent, respectively, and the molar concentration of the divalent ion in the redox pair is greater than the molar concentration of the trivalent ion.

[0007] In some possible embodiments, based on the total molar amount of the two ions in the redox pair, the molar concentration of the divalent ion is 60% to 100%.

[0008] In some possible embodiments, the two ions in the redox pair are two oxidation states of the same element.

[0009] In some possible embodiments, the chemical formula of the coating layer is Li 1+x M y N 1-x-y O2-z F z where \(0 \lt x\leq1\), \(0 \lt y\leq1\), \(0 \lt z\lt2\), the M element is the first coating element, and the M element includes at least one of Co, Ni, and Mn; the N element is the second coating element, and the N element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

[0010] In some possible embodiments, the chemical formula of the core is Li e Ni a Co b Mn c Q d O₂, where \(0.7\leq e\leq1.05\), \(0.6\leq a\leq1.0\), \(0\leq b\leq0.3\), \(0\leq c\leq0.3\), \(0\leq d\leq0.05\), and the Q element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

[0011] The embodiment of the present application also provides a preparation method of a ternary cathode material, and the preparation method includes the following steps: Mix a nickel-cobalt-manganese precursor and a first lithium source to obtain a primary mixture; Perform a primary sintering on the primary mixture to obtain the core of the ternary cathode material; Mix the core, a second lithium source, a coating agent, and a fluorine-containing compound to obtain a secondary mixture, where the coating agent contains a first coating element; and Perform a secondary sintering on the secondary mixture to form a coating layer on the surface of the core, thereby obtaining the ternary cathode material, where the coating layer has a cation-disordered rock-salt phase structure, the first coating element exists in the form of a redox pair in the coating layer, the valence states of the two ions in the redox pair are divalent and trivalent respectively, and the molar concentration of the divalent ion in the redox pair is greater than that of the trivalent ion.

[0012] In some possible embodiments, the mass ratio of lithium element in the second lithium source, the first coating element, and fluorine element in the fluorine-containing compound is \((2 - 10):(10 - 60):(2 - 20)\).

[0013] In some possible embodiments, the temperature of the secondary sintering is \(500^{\circ}C - 1000^{\circ}C\), and the time of the secondary sintering is \(6h - 16h\).

[0014] In some possible embodiments, the secondary sintering includes a first sintering stage and a second sintering stage. The heating rate of the first sintering stage is 2°C / min to 8°C / min, the temperature is 500°C to 800°C, and the heat preservation time is 4h to 8h. The heating rate of the second sintering stage is 3°C / min to 15°C / min, the temperature is 850°C to 1000°C, and the heat preservation time is 0.5h to 2h.

[0015] In some possible embodiments, the chemical formula of the coating layer is Li 1+x M y N 1-x-y O 2-z F z , 0 < x ≤ 1, 0 < y ≤ 1, 0 < z < 2. The M element is the first coating element, and the M element includes at least one of Co, Ni, and Mn. The N element is the second coating element, and the N element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

[0016] In some possible embodiments, the temperature of the primary sintering is 800°C to 1000°C, and the time of the primary sintering is 8h to 24h.

[0017] In addition, the embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The positive electrode plate includes a positive electrode active material, and the positive electrode active material is the aforementioned ternary positive electrode material.

[0018] Compared with the prior art, the ternary positive electrode material provided by the embodiment of the present application in-situ constructs a coating layer with a cation-disordered rock salt phase structure on the surface of the core. First, the cation-disordered rock salt phase structure enables the coating layer to have a three-dimensional face-centered cubic oxygen lattice. Among them, lithium ions are easy to diffuse through the tetrahedral site network with a low energy barrier without causing large stress changes, which can improve the structural stability of the coating layer. At the same time, it can also inhibit the overall lattice distortion of the ternary positive electrode material caused by stress changes in the bulk phase, thereby improving the structural stability of the ternary positive electrode material and reducing the generation of cracks during cycling and the interfacial side reactions caused by the contact between the core and the electrolyte. Second, the introduction of redox pairs in the coating layer can be between ions in two valence states (M 3+ / M 2+) forms a path for electron jumping and can generate a built-in electric field effect, thereby improving the diffusion kinetics of electrons and ions, reducing the charge transfer impedance, and increasing the lithium ion diffusion rate. In addition, the coating layer of the ternary cathode material contains low-valent divalent ions. During the charging and de-lithiation process, the divalent ions will first be oxidized to trivalent ions, reducing the proportion of high-valent ions on the surface of the cathode material under the high-voltage and high-de-lithiation charging state, reducing the risk of reaction with the electrolyte from the source, and improving the interface stability of the ternary cathode material under high voltage conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A process flow chart of a method for preparing a ternary positive electrode material provided in one embodiment of the present application.

[0020] Figure 2 A schematic diagram of the structure of an electrochemical device provided in one embodiment of the present application.

[0021] Figure 3 This is the XPS spectrum of the cobalt element on the surface of the ternary positive electrode material provided in Example 1 of the present application.

[0022] Figure 4 This is the XPS spectrum of the nickel element on the surface of the ternary positive electrode material provided in Example 1 of the present application.

[0023] Figure 5 This is the XPS spectrum of the cobalt element on the surface of the ternary positive electrode material provided in Comparative Example 1 of the present application.

[0024] Figure 6 XPS spectrum of nickel element on the surface of the ternary positive electrode material provided in Comparative Example 1 of the present application.

[0025] Figure 7 This is a test chart of the cycle performance of batteries prepared with the ternary positive electrode materials provided in Examples 1-5 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION

[0026] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0027] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the implementation methods of this application and the features in the implementation methods can be combined with each other unless there is a conflict; many specific details are elaborated in the following description to facilitate a full understanding of this application, and the described implementation methods are only part of the implementation methods of this application, rather than all of the implementation methods.

[0028] An embodiment of the present application provides a ternary positive electrode material, which includes: an inner core and a coating layer located on the surface of the inner core, wherein the coating layer has a cationic disordered salt rock phase structure, wherein the coating layer contains a first coating element, and the first coating element exists in the form of a redox pair, and the valence states of the two ions in the redox pair are divalent and trivalent, respectively, and the molar concentration of the divalent ion in the redox pair is greater than the molar concentration of the trivalent ion.

[0029] Compared with the ordered layered structure of the core of the ternary positive electrode material, the coating layer of the ternary positive electrode material has a cationic disordered salt rock phase structure. This structure has a face-centered cubic oxygen lattice. The lithium ions and transition metal ions in the lattice are in a disordered state. The lithium ions and transition metal ions randomly occupy the 4a position of the face-centered cubic oxygen lattice, and the lithium ions can diffuse efficiently through the tetrahedral site network with a low energy barrier.

[0030] The advantages of the cationic disordered salt rock phase structure are mainly reflected in the following aspects: First, the two-dimensional layered structure of the inner core will produce anisotropic stress changes when lithium ions are extracted and deintercalated. Unlike the two-dimensional layered structure of the inner core, the coating layer of the disordered rock salt phase structure has a three-dimensional face-centered cubic oxygen lattice. In this three-dimensional face-centered cubic oxygen lattice structure, the extraction and insertion of lithium ions will hardly cause stress changes, and the lattice strain of the coating layer can be ignored, which can not only improve the structural stability of the coating layer, but also reduce the overall lattice distortion of the ternary positive electrode material caused by stress changes in the bulk phase, reduce the risk of cracks during the cycle, and thus reduce the interface side reactions caused by the fresh interface generated by the cracks being directly exposed to the electrolyte.

[0031] Secondly, the introduction of the divalent and trivalent redox pairs of the first coating element in the coating layer can form a path for electron hopping between the two valence states of ions, while generating a built-in electric field effect. This helps to improve the diffusion kinetics of electrons and ions, reduce the charge transfer impedance, and reduce the kinetic loss caused by the obstruction of the ion transmission path due to the disordered cations in the coating layer, thereby increasing the lithium ion diffusion rate.

[0032] In addition, during the charge and discharge process, especially at high operating voltage, the transition metal on the surface of the ternary cathode material will be oxidized and in a high valence state (trivalent and / or tetravalent). For example, nickel will be Ni 4+ Existence, cobalt will be Co 4+exists. The high-valent ions at this time have strong oxidizing properties and are prone to redox reactions with the electrolyte, which in turn leads to a series of problems such as electrolyte decomposition, transition metal dissolution, and lattice oxygen escape. In the coating layer of the ternary positive electrode material provided in the embodiment of the present application, the molar concentration of divalent ions in the redox pair is greater than the molar concentration of trivalent ions, that is, low-valent divalent metal ions are dominant. As charging and delithiation proceed, divalent ions will first be oxidized to trivalent ions, which directly reduces the proportion of high-valent ions on the surface under high-voltage and high-delithiation charging conditions, thereby reducing the above-mentioned series of problems caused by side reactions between ions in high oxidation states and electrolytes from the source, and improving the surface stability of the ternary positive electrode material.

[0033] In some embodiments, the molar concentration of divalent ions can be 60% to 100% based on the total molar amount of the two ions in the redox pair, that is, the divalent ions in the redox pair account for 60% to 100% of the total molar amount of divalent ions and trivalent ions. This shows that the first coating element in the coating layer is mainly in a low-valent state, which delays the transition of the first coating element in the coating layer to a high-valent state, further reducing the proportion of high-valent ions on the surface of the ternary positive electrode material in the charged state, thereby further improving the surface stability of the ternary positive electrode material. The molar concentration of divalent ions can further be 70% to 100%, and can be exemplarily 60%, 62%, 65%, 68%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or any value within the numerical range composed of any two of the above values.

[0034] Furthermore, the two ions in the redox pair can be two oxidation states of the same element, that is, the first coating element includes at least one element, and the molar concentration of the divalent ion can be 60% to 100%, and further can be 70% to 100%, and illustratively can be 60%, 62%, 65%, 68%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or any value within the numerical range composed of any two of the above values, based on the total molar amount of the two oxidation states (divalent and trivalent) of the same element in the redox pair.

[0035] It should be noted that the molar concentration of the ions in the above-mentioned coating layer is measured by X-ray photoelectron spectrometer (XPS), and the measurement process can be specifically as follows: Al-Kα is used as the ray source (energy hν=1486.6eV), and the Cls peak binding energy 284.80eV is used as the charge correction standard; the fine spectrum of M 2p and / or 3s is further analyzed, and deconvolution is performed according to the unified characteristic peak position to obtain M 2+ The relative proportion of 2+ / (M 2+ + M 3+ )).

[0036] In some embodiments, the chemical formula of the coating layer can be Li 1+x M y N 1-x-y O 2-z F z , where 0 < x ≤ 1, 0 < y ≤ 1, 0 < z < 2. Among them, the first coating element M can include at least one of Co, Ni, and Mn, and the second coating element N is a doping element of the coating layer. N can include at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca. The second coating element N in the coating layer can further optimize the coating layer structure stability, interface stability, ion diffusion performance, and cycling performance of the ternary cathode material, etc.

[0037] In some embodiments, the chemical formula of the core can be Li e Ni a Co b Mn c Q d O2, where 0.7 ≤ e ≤ 1.05, 0.6 ≤ a ≤ 1.0, 0 ≤ b ≤ 0.3, 0 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.05. Q is a doping element of the core. The Q element can include at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca, etc. The doping element Q in the core can further optimize the structure stability, ion diffusion performance, and cycling performance of the ternary cathode material, etc. For example, Zr, Al, Ti, Nb, or Y, etc. can improve the lattice stability of the ternary cathode material and reduce lattice distortion; Ti or Zr can enhance the thermal stability of the ternary cathode material; elements such as Ti, Nb, W, or Ta help to form lithium-ion diffusion channels and improve the charge and discharge rate; Al, Zr, or La, etc. can react with the components in the electrolyte to form a more stable electrode / electrolyte interface and reduce side reactions; Mo, V, or Cr, etc. are beneficial to improving the conductivity of the ternary cathode material, etc.

[0038] The cathode material of the embodiments of the present application forms the aforementioned coating layer on the surface of the core. This coating layer has a cation-disordered rock-salt phase, and the redox pair in the coating layer is mainly divalent ions, which can effectively reduce the interface side reactions during the charge and discharge process of the cathode material, especially in high-voltage working scenarios, and improve the structure stability. Through the unique structure design of the coating layer, problems such as structural lattice strain and structural collapse during the cycling process are reduced, the diffusion kinetics of electrons and ions are improved, and at the same time, the interface stability of the ternary cathode material is improved, thereby increasing the cycle life of the battery prepared from the ternary cathode material and meeting the usage requirements of high voltage.

[0039] Please refer to Figure 1As shown, the embodiment of the present application also provides a method for preparing a ternary positive electrode material, which specifically includes the following steps: Step S1, mixing a nickel-cobalt-manganese precursor and a first lithium source to obtain a primary mixture.

[0040] In some embodiments, the ratio of the molar number of lithium in the first lithium source to the total molar number of transition metals in the nickel-cobalt-manganese precursor can be (0.7-1.05):1, the molar ratio can further be (0.9-1.03):1, further can be (0.95-1.03):1, further can be (0.95-1.0):1, and further can be (0.95-1.0):1, illustratively can be 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1.0:1, 1.05:1 or any value within the numerical range composed of any two of the above values.

[0041] In some embodiments, the first lithium source may include at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, lithium oxide, lithium citrate, and the like.

[0042] In some embodiments, a dopant may be added to the primary mixture, wherein the dopant contains a core doping element Q, and the core doping element Q is independently selected from at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La and Ca.

[0043] In some embodiments, the mixing method may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the nickel-cobalt-manganese precursor and the lithium source. It is understood that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the nickel-cobalt-manganese precursor and the lithium source is possible.

[0044] Step S2, sintering the primary mixture to obtain the core of the ternary positive electrode material.

[0045] In some embodiments, the primary sintering temperature may be 800°C to 1000°C, and the primary sintering time may be 8h to 24h. By controlling the primary sintering temperature and time, the crystal structure of the core of the ternary cathode material is optimized, which is beneficial to improving the rate performance and cycle performance of the ternary cathode material.

[0046] In some embodiments, the primary sintering atmosphere may be an oxygen-containing atmosphere, which is beneficial to promoting the oxidation reaction of the nickel-cobalt-manganese precursor and improving the electrochemical performance and stability of the core. The primary sintering atmosphere may further be an atmosphere with an oxygen concentration of 50% or more, and the oxygen concentration of the oxygen-containing atmosphere may be 50%, 55%, 60%, 70%, 80%, 83%, 85%, 90%, 95%, 100% or any value within the numerical range consisting of any two of the above values.

[0047] Step S3, mixing the core, the second lithium source, the coating agent and the fluorine-containing compound to obtain a secondary mixture, wherein the coating agent contains the first coating element.

[0048] In this step, the second lithium source, the coating agent and the fluorine-containing compound are mixed as coating materials on the surface of the inner core to form a secondary mixture. Based on the lower molar ratio of lithium and nickel, cobalt and manganese metal elements in step S1, the second lithium source is added to the secondary mixture to introduce lithium elements again, which is conducive to optimizing the coating material ratio and subsequently forming a coating layer with a disordered rock salt phase structure.

[0049] In some embodiments, the mass ratio of lithium in the second lithium source, the first coating element, and the fluorine in the fluorine-containing compound can be (2-10): (10-60): (2-20). This ratio introduces excess lithium and fluorine into the coating material, which is beneficial to further optimize the structure of the coating layer and adjust the proportion of divalent ions in the redox pair. It can be understood that the proportion of divalent ions in the redox pair can be increased to greater than or equal to 60%. The mass ratio can further be (2-5): (10-60): (10-20), and can be exemplarily 2:10:2, 2:30:2, 2:20:10, or any value within the range of (2-10): (10-60): (2-20).

[0050] In some embodiments, the mass ratio of the core to the lithium element in the second lithium source can be 1: (0.002-0.01), thereby controlling the mass ratio of the core to the coating material, which is conducive to obtaining a coating layer with moderate thickness. The mass ratio can further be 1: (0.003-0.008), and can be exemplarily 1: 0.002, 1: 0.003, 1: 0.004, 1: 0.005, 1: 0.006, 1: 0.007, 1: 0.008, 1: 0.01 or any value within the numerical range composed of any two of the above values.

[0051] In some embodiments, the first coating element may include at least one of Co, Ni and Mn. It is understandable that the coating agent may be a compound containing the first coating element, and the coating agent may include at least one of a Co-containing compound, a Ni-containing compound, a Mn-containing compound, a Ni, Co-containing compound, a Ni, Mn-containing compound, a Mn, Co-containing compound, and a Ni, Co, Mn-containing compound.

[0052] In some embodiments, the Co-containing compound may include at least one of cobalt hydroxide, cobalt oxyhydroxide, cobalt oxide, cobalt trioxide, cobalt acetate, cobalt carbonate, cobalt oxalate, and the like.

[0053] In some embodiments, the Ni-containing compound may include at least one of nickel oxide, nickel hydroxide, nickel nitrate, nickel phosphate, and the like.

[0054] In some embodiments, the Mn-containing compound may include at least one of manganese oxide, manganous oxide, manganese nitrate, and the like.

[0055] In some embodiments, the coating agent containing two or three first coating elements may include at least one of amorphous nickel cobalt oxide, nickel cobalt phosphide, and nickel cobalt manganese oxide. It can be understood that the coating agent includes but is not limited to the above compounds.

[0056] In some embodiments, the second lithium source may include at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, lithium oxide, lithium citrate, and the like.

[0057] In some embodiments, the fluorine-containing compound may be an inorganic metal fluoride, and the inorganic metal fluoride may include at least one of lithium fluoride, magnesium fluoride, zirconium fluoride, and aluminum fluoride.

[0058] In some embodiments, a coating agent containing a second coating element may be added to the secondary mixture, and the second coating element is independently selected from at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La and Ca. Adding the second coating element to the secondary mixture is beneficial to further improve the conductivity and structural stability of the coating layer formed by the coating material and reduce the side reaction with the electrolyte.

[0059] Step S4, performing secondary sintering on the secondary mixture to form a coating layer on the surface of the inner core, thereby obtaining a ternary positive electrode material.

[0060] Specifically, the secondary mixture is subjected to secondary sintering to form a coating layer on the surface of the inner core, thereby obtaining a ternary positive electrode material, wherein the coating layer has a cationic disordered rock salt phase structure, and the first coating element exists in the coating layer in the form of a redox pair, the valence states of the two ions in the redox pair are divalent and trivalent, respectively, and the molar concentration of the divalent ions in the redox pair is greater than the molar concentration of the trivalent ions. First, the formation of the coating layer is conducive to introducing the first coating element into the surface of the ternary positive electrode material. Secondly, the addition of the second lithium source and the fluorine-containing compound in the coating layer is conducive to the formation of a coating layer with a disordered rock salt phase structure, and the redox pair of the first coating element in the coating layer is mainly divalent ions through charge balance. The introduction of fluorine-containing compounds is also conducive to improving the conductivity and electrochemical stability of the ternary positive electrode material and optimizing the interface structure.

[0061] In some embodiments, the chemical formula of the coating layer is Li 1+x M y N1-x-y O 2-z F z where 0 < x ≤ 1, 0 < y ≤ 1, 0 < z < 2, the M element is the first coating element, the M element includes at least one of Co, Ni, and Mn, the M exists in the form of a redox pair, the valence states of the redox pair are divalent and trivalent, and the molar concentration of the divalent ions in the redox pair of the same element is greater than that of the trivalent ions. The N element is the second coating element, and the N element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

[0062] In some embodiments, during the secondary sintering process, some of the transition metal elements (Co, Ni, and Mn) in the core will partially diffuse into the coating layer. Under the regulation of charge balance, the molar concentration of divalent ions in the transition metal elements diffused into the coating layer is also greater than that of trivalent ions, forming a redox pair mainly composed of divalent ions.

[0063] In some embodiments, the atmosphere for secondary sintering can be an oxygen-containing atmosphere to promote the secondary sintering reaction and facilitate the formation of the phase structure of the coating layer. Further, the atmosphere for secondary sintering can be an atmosphere with an oxygen concentration of more than 50%. Exemplarily, the oxygen concentration of the oxygen-containing atmosphere can be any value within the numerical range composed of any two values among 50%, 55%, 60%, 65%, 70%, 75%, 80%, 83%, 85%, 90%, 95%, 100%, or above.

[0064] In some embodiments, the temperature for secondary sintering can be 500°C to 1000°C, further can be 650°C to 850°C, and exemplarily can be 500°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, or 1000°C, etc.; the time for secondary sintering can be 6 h to 16 h, further can be 8 h to 14 h, and exemplarily can be 6 h, 8 h, 10 h, 12 h, 14 h, or 16 h, etc. The secondary sintering conditions of sintering at 500°C to 1000°C for 6 h to 16 h are beneficial to further forming a coating layer with good quality, uniform distribution, and a disordered rock salt phase structure.

[0065] Further, the secondary sintering may include a first sintering stage and a second sintering stage, wherein the heating rate of the first sintering stage is 2°C / min~8°C / min, the temperature is 500°C~800°C, and the holding time is 4h~8h, and the heating rate of the second sintering stage is 3°C / min~15°C / min, the temperature is 850°C~1000°C, and the holding time is 0.5h~2h. The curve of the secondary sintering forms a coating layer of disordered rock salt phase structure on the surface of the inner core through the first sintering stage with a lower sintering temperature and a longer holding time; and then promotes the bonding of the coating layer with the inner core through the second sintering stage with a higher sintering temperature and a shorter holding time, while retaining the disordered rock salt phase structure of the coating layer. The sintering curve of the secondary sintering is conducive to further forming a coating layer of good quality, and enhancing the bonding force between the coating layer and the inner core, effectively reducing the risk of the coating layer falling off, and improving the structural stability of the ternary positive electrode material.

[0066] In some embodiments, after secondary sintering, the temperature can be cooled to room temperature at a cooling rate of 3°C / min to 15°C / min. The slow cooling process has an annealing effect, which can reduce the thermal stress generated by rapid cooling of the ternary positive electrode material and reduce the formation of cracks between the coating layer and the core.

[0067] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By selecting the second lithium source, coating agent and fluorine-containing compound as coating materials, it is beneficial to form a coating layer with a disordered rock salt phase structure, and the valence state of the first coating element in the redox pair is mainly divalent through charge balance, thereby improving the cycle life and structural stability of the battery prepared by the ternary positive electrode material. The proportion of divalent ions in the redox pair can also be further adjusted by controlling the amount of lithium and fluorine in the coating material.

[0068] 2. The temperature and time of secondary sintering are conducive to forming a coating layer with good quality and uniform distribution of disordered rock salt phase structure. In addition, a two-stage sintering curve of first low-temperature long-time sintering and then high-temperature short-time sintering can be used to further improve the quality of the coating layer and the bonding strength between the coating layer and the core, and further improve the structural stability of the ternary positive electrode material.

[0069] 3. The preparation method is simple and efficient, which is conducive to the large-scale production of ternary positive electrode materials and has excellent commercial prospects.

[0070] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the positive electrode plate 10 includes a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described above.

[0071] The electrochemical device 100 prepared using the aforementioned ternary cathode material has the advantages of high cycle performance, high stability, and high energy density.

[0072] The above-mentioned ternary positive electrode material and its preparation method and electrochemical device are further described below through specific examples.

[0073] Example 1 Step 1: Ni-Co-Mn precursor Ni 0.65 Co 0.7 Mn 0.28 (OH)2, lithium hydroxide, ZrO2 and Al2O3 are mixed in a high-speed mixer to obtain a primary mixture, in which the molar ratio of Li to the transition metal in the nickel-cobalt-manganese precursor is 0.98:1, ZrO2 and Al2O3 are dopants, the mixing speed is 500 r / min, and the mixing time is 20 min.

[0074] Step 2: sinter the primary mixture in an atmosphere of 85% oxygen at 970° C. for 24 hours to obtain the core of the ternary positive electrode material.

[0075] Step 3, the core, lithium hydroxide, cobalt tetroxide containing the first coating element, lithium fluoride and coating agent niobium oxide are mixed in a high-speed mixer to obtain a secondary mixture, wherein the mass ratio of lithium element, cobalt element, fluorine element and niobium element in the core and lithium hydroxide is 1:0.006:0.02:0.01:0.002, the mixing speed is 600r / min, and the mixing time is 20min.

[0076] Step 4: In a 75% oxygen atmosphere, the secondary mixture is heated to 650°C at a heating rate of 3°C / min and kept warm for 8 hours, then heated to 850°C at a heating rate of 12°C / min and kept warm for 1 hour, then cooled to room temperature at a cooling rate of 10°C / min, and evenly crushed by low-intensity mechanical means to obtain a ternary positive electrode material.

[0077] Example 2 The difference between Example 2 and Example 1 is that in step 3, the mass ratio of lithium, cobalt, fluorine and niobium in the core and lithium hydroxide is 1:0.002:0.02:0.01:0.002. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0078] Example 3 The difference between Example 3 and Example 1 is that in step 3, the mass ratio of lithium, cobalt, fluorine and niobium in the core and lithium hydroxide is 1:0.006:0.01:0.01:0.002. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0079] Example 4 The difference between Example 4 and Example 1 is that in step 3, the coating agent is molybdenum oxide. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0080] Example 5 The difference between Example 5 and Example 1 is that: Step 4 is to heat the secondary mixture to 650°C at a heating rate of 3°C / min and keep it for 8 hours under 75% oxygen atmosphere, then cool it to room temperature at a cooling rate of 5°C / min, and evenly disperse it by low-intensity mechanical crushing to obtain a ternary positive electrode material. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be repeated here.

[0081] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step 3, the core, lithium hydroxide, cobalt trioxide and coating agent niobium oxide are mixed in a high-speed mixer without adding lithium fluoride to obtain a secondary mixture. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0082] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that in step 3, the core, cobalt trioxide, lithium fluoride and coating agent niobium oxide are mixed in a high-speed mixer without adding lithium hydroxide to obtain a secondary mixture. The preparation method of the remaining ternary positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0083] 1. The following tests were performed on the ternary positive electrode materials and the batteries prepared in Examples 1-5 and Comparative Examples 1-2.

[0084] (I) The chemical valence state of the ternary cathode materials obtained in Examples 1-5 and Comparative Examples 1-2 was measured, and the results are shown in Table 1. The surface Co valence state test results in Example 1 are as follows: Figure 3 As shown, the surface Ni valence test results are as follows Figure 4 As shown; the surface Co valence test results in Comparative Example 1 are as follows Figure 5 As shown, the surface Ni valence test results are as follows Figure 6 shown.

[0085] The measurement was carried out by X-ray photoelectron spectrometer (XPS). The specific test process is as follows: Al-Kα is used as the ray source (energy hν = 1486.6eV) to etch the surface of the material. The etching depth is the surface and 10nm deep. The C1s peak binding energy of 284.80eV is used as the charge correction standard; the fine spectra of Co 2p and Ni 2p in the obtained energy spectrum are further analyzed, and deconvolution is performed according to the unified characteristic peak position to obtain the relative proportions of different chemical valence states of Co and Ni.

[0086] (II) The electrical performance test conditions are as follows: the ternary positive electrode materials, superconducting carbon black SP and polyvinylidene fluoride PVDF prepared in Examples 1-5 and Comparative Examples 1-2 are mixed in a mass ratio of 94:3:3, and the mixture is adjusted into a slurry with N-methyl-pyrrolidone (NMP); the slurry is evenly coated on an aluminum foil current collector to obtain a positive electrode film. A metal lithium sheet is used as the negative electrode, a polypropylene microporous membrane is used as the separator, and 1 mol / LiPF6 (the solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) is used as the electrolyte, and button cells are assembled in an Ar gas-protected glove box.

[0087] The button cell prepared above was subjected to a capacity test under the following test conditions: at 25°C, a voltage range of 2.8V to 4.5V, a charge and discharge rate of 0.1CV / 0.1CD, and the charge and discharge specific capacity and coulombic efficiency were measured. The results are shown in Table 2.

[0088] The button cell prepared above was subjected to a cycle capacity test under the following conditions: at 45°C, the voltage range was 2.5-4.5V, the charge and discharge rate was 0.5CV / 1.0CD, and the cycle was 50 cycles. The capacity retention rate after 50 cycles was measured. The results are shown in Table 2 and Figure 7 shown.

[0089] Combined with Table 1 Figures 3 to 6 The results show that the concentration of divalent ions of Co and Ni elements in the surface (coating layer) of Examples 1-5 is greater than the concentration of trivalent ions, indicating that Co and Ni are mainly present in divalent form in the coating layer of the ternary positive electrode material prepared in Examples 1-5, that is, the coating element M in the coating layer is mainly in a low-valent state, while the coating element M in the coating layer of the ternary positive electrode material prepared in Comparative Examples 1-2 is mainly in a high-valent state. This is because no cationic disordered salt rock phase structure and redox pair are formed in the coating layer of the positive electrode materials of Comparative Examples 1 and 2, among which, no fluorine-containing compound is added in Comparative Example 1, and no second lithium source is added in Comparative Example 2, so the valence state of the first coating element in the coating layer cannot be effectively regulated.

[0090] Combined with Table 2 Figure 7 The results show that compared with Comparative Examples 1-2, the batteries made of the ternary positive electrode materials in Examples 1-5 have good charge and discharge capacity, efficiency and capacity retention rate. Among them, it can be seen from Example 1 and Comparative Examples 1-2 that the Co element and Ni element in the coating layer of the ternary positive electrode material obtained in Example 1 are mainly divalent, which reduces the side reaction with the electrolyte and enhances the surface stability of the ternary positive electrode material, so that the efficiency and capacity retention rate of the corresponding battery are significantly improved, and the cycle performance of the battery is improved.

[0091] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A ternary positive electrode material, characterized in that: include: An inner core and a coating layer located on the surface of the inner core, wherein the coating layer has a cationic disordered salt rock phase structure, wherein the coating layer contains a first coating element, the first coating element exists in the form of a redox pair, the valence states of the two ions in the redox pair are divalent and trivalent, respectively, and the molar concentration of the divalent ion in the redox pair is greater than the molar concentration of the trivalent ion.

2. The ternary cathode material according to claim 1, characterized in that: The molar concentration of the divalent ion is 60% to 100% based on the total molar amount of the two ions in the redox pair.

3. The ternary cathode material according to claim 2, characterized in that: The two ions in the redox pair are two oxidation states of the same element.

4. The ternary cathode material according to claim 1, characterized in that: The chemical formula of the coating layer is Li 1+ x M y N 1-x-y O 2-z F z , where 0 < x ≤ 1, 0 < y ≤ 1, 0 < z < 2, the M element is the first coating element, and the M element includes at least one of Co, Ni, and Mn; the N element is the second coating element, and the N element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

5. The ternary cathode material according to claim 1, characterized in that: The chemical formula of the core is Li e Ni a Co b Mn c Q d O2, wherein 0.7≤e≤1.05, 0.6≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, 0≤d≤0.05, and the Q element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La and Ca.

6. A method for preparing a ternary positive electrode material, characterized in that: include: Mixing a nickel-cobalt-manganese precursor and a first lithium source to obtain a primary mixture; Sintering the primary mixed material to obtain the core of the ternary positive electrode material; The core, the second lithium source, the coating agent and the fluorine-containing compound are mixed to obtain a secondary mixture, wherein the coating agent contains the first coating element; and The secondary mixture is subjected to secondary sintering to form a coating layer on the surface of the inner core, thereby obtaining the ternary positive electrode material, wherein the coating layer has a cationic disordered salt rock phase structure, and the first coating element exists in the coating layer in the form of a redox pair, the valence states of the two ions in the redox pair are divalent and trivalent, respectively, and the molar concentration of the divalent ion in the redox pair is greater than the molar concentration of the trivalent ion.

7. The method for preparing a ternary cathode material according to claim 6, characterized in that: The mass ratio of the lithium element in the second lithium source, the first coating element and the fluorine element in the fluorine-containing compound is (2-10): (10-60): (2-20).

8. The method for preparing the ternary cathode material according to claim 6, characterized in that: The secondary sintering includes a first sintering stage and a second sintering stage. The heating rate of the first sintering stage is 2°C / min~8°C / min, the temperature is 500°C~800°C, and the insulation time is 4h~8h. The heating rate of the second sintering stage is 3°C / min~15°C / min, the temperature is 850°C~1000°C, and the insulation time is 0.5h~2h.

9. The method for preparing a ternary cathode material according to claim 6, characterized in that: The chemical formula of the coating layer is Li 1+x M y N 1-x-y O 2-z F z , where 0 < x ≤ 1, 0 < y ≤ 1, 0 < z < 2. The M element is the first coating element, and the M element includes at least one of Co, Ni, and Mn. The N element is the second coating element, and the N element includes at least one of Zr, Al, Sr, W, Nb, Mo, Ti, Ta, Sb, Y, V, Cr, La, and Ca.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is a ternary positive electrode material as described in any one of claims 1 to 5 or a ternary positive electrode material prepared by the preparation method of a ternary positive electrode material as described in any one of claims 6 to 9.